Leveraging Artificial Intelligence for Sustainable Electronics Manufacturing Supply Chains - Gautam Nandkishore Nayak, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical article examines the transformative role of Artificial Intelligence in developing sustainable supply chains within the electronics manufacturing sector. The article explores how AI technologies are revolutionizing sustainability practices across the industry, from resource optimization to waste management. By analyzing current challenges, AI-enabled solutions, and implementation frameworks, this research demonstrates how advanced technologies are enabling manufacturers to achieve significant improvements in environmental performance while maintaining operational efficiency. The article encompasses various aspects of sustainability, including supply chain transparency, resource utilization, carbon footprint reduction, and organizational transformation, providing a comprehensive overview of how AI is reshaping the future of sustainable electronics manufacturing.
Keywords: Artificial Intelligence in Manufacturing; Environmental Impact Reduction; Industry 4.0 Implementation; Smart Manufacturing Infrastructure; Sustainable Electronics Supply Chain